ANALISIS HUKUM PIDANA TERHADAP TINDAK PIDANA PENCEMARAN LINGKUNGAN DAN/ATAU DEGRADASI LINGKUNGAN - Gregorius Ricky Yulianto; Sunariyo Sunariyo; Aulia Vivi Yulianingrum (Collegium Studiosum Journal, 2026)
Environmental pollution and/or environmental degradation caused by corporations constitutes a serious challenge in law enforcement in Indonesia. The case involving PT Indominco Mandiri in Santan Village, Kutai Kartanegara, concerning the unauthorized dumping of hazardous and toxic waste (B3), as adjudicated in Decision Number 526/Pid.Sus-LH/2017/PN.Trg, reveals persistent deficiencies in the application of corporate criminal liability. Although such liability has been normatively regulated under Law Number 32 of 2009 on Environmental Protection and Management, its enforcement in practice remains suboptimal in generating deterrent effects and ensuring sustainable environmental protection. Accordingly, this study is undertaken to provide an in-depth examination of the application of criminal law to corporate environmental offenses. This research employs a normative juridical method, utilizing both a statutory approach and a case approach. The data consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The statutory approach involves an examination of the provisions set forth in Law Number 32 of 2009, particularly those concerning corporate criminal liability, while the case approach focuses on the judicial analysis of the decision involving PT Indominco Mandiri. The findings indicate that the court applied Article 104 in conjunction with Article 116 of Law Number 32 of 2009 in establishing corporate criminal liability. However, the sanction imposed, namely a fine of IDR 2,000,000,000, is deemed insufficient to produce an optimal deterrent effect and does not reflect a progressive approach to environmental law enforcement. Furthermore, challenges persist in proving corporate fault (mens rea), alongside a tendency to prioritize financial penalties over custodial sanctions against corporate executives, and a lack of integration among criminal, administrative, and civil enforcement mechanisms. Therefore, strengthening legal instruments is necessary, including the imposition of additional criminal sanctions such as license revocation and the enforcement of personal liability against corporate managers. In addition, the integration of repressive and restorative approaches should be prioritized to ensure legal accountability while simultaneously facilitating environmental restoration.